A General Stochastic Volatility Model for the Pricing of Interest Rate Derivatives - Trolle, Anders B.; Schwartz, Eduardo S. (Review of Financial Studies, 2009)
We develop a tractable and flexible stochastic volatility multifactor model of the term structure of interest rates. It features unspanned stochastic volatility factors, correlation between innovations to forward rates and their volatilities, quasi-analytical prices of zero-coupon bond options, and dynamics of the forward rate curve, under both the actual and risk-neutral measures, in terms of a finite-dimensional affine state vector. The model has a very good fit to an extensive panel dataset of interest rates, swaptions, and caps. In particular, the model matches the implied cap skews and the dynamics of implied volatilities.